Kebangkitan timbal balas perkauman dalam politik Malaysia - Zakaria, Jazimin; Zamhury, Nurulaini (Journal of Islamic, Social, Economics and Development, 2025)
This article examines the phenomenon of racial reciprocity or counter racism in the context of ethnic politics in Malaysia, employing a qualitative approach to assess its implications for the country's social integration. Malaysia was formed in the context of a diverse society as a result of the history of British colonialism that brought in large-scale ethnic Chinese and Indian migrations in the early 20th century. This colonial policy not only solved the problem of the British labor shortage but also changed the ethnic composition of Malaya as a whole. After the Second World War, the weakening of British influence opened the door to demands for independence. However, the process was accompanied by the establishment of power sharing among Malays, Chinese, and Indians through the adoption of the principles of jus soli and the social contract. The high tolerance shown by ethnic Malays is fundamental to the survival of the bangsa Malaysia project, but also raises concerns about its long-term implications. After 1957, the political structure that still inherited elements of the British administration maintained social and economic disparities as a result of the policy of division and order. These tensions peaked in the 1969 elections until the May 13 tragedy, which exposed racial reciprocity between political parties and ethnic groups. Racial retribution or reciprocal racism persists to this day, operating under the guise of democracy that fails to accommodate the historical context of this nation while neglecting the concept of a Bangsa Malaysia